Analisis Dan Perancangan Sistem Informasi Penjualan Rumah Pada PT. Zaki Putra Andalas - Irawan, Dodi; Roestam, Rusdianto (LPPM Universitas Dinamika Bangsa, 2020)
PT. Zaki Putra Andalas is one of the companies engaged in housing developers in processing data on home sales does not have a good system. This research aims to design information systems according to current technological developments with a web-based in order to increase revenue from sales and save time in the sales process, where sales will be made online. Systems development uses the Unified Modeling Language (UML) model approach. The system model used is the Use Case Diagram, Activity Diagram and Class Diagram. This research resulted in a prototype of a housing sales information system at PT. Zaki Putra Andalas web-based that can be further implemented so as to produce a sales information system that can be applied to PT. Zaki Putra Andalas. This system prototype needs to be developed so that it can really be applied to PT. Zaki Putra Andalas to support better management of all business processes at PT. Zaki Putra Andalas.